Measuring the Concentration of Nitrate and Nitrite Ions in Drinking Water and Carcinogenic Risk Assessment in the Urban Water Distribution Network System of Evaz City, Fars Province, Iran - Mohammad Reza Zare; Mohammad Reza Shooshtarian; Jahangir Otofat Shoare Jahromi; Marzieh Honarbakhsh; Mahvash Haghjoo; Fatemeh Hosseini; Jamal Mehralipour; zohreh berizi (Mashhad University of Medical Sciences, 2020)
Background and aim: Today, the supply of qualified drinking water has become the main concern of the competent authorities. Drinking water, in addition to the appropriate quantity, must have appropriate standards regarding physicochemical and microbial properties. Nitrate and nitrite ions are of special importance due to their adverse environmental and health. The aim of this study was to determine the concentration of these ions in the drinking water of Evaz city and to perform calculations related to health risk assessment. Method: In this study, five points were selected and 50 samples (10 samples from each point) were collected over time intervals. After transferring the samples to the environmental chemistry laboratory, the concentration of nitrate and nitrite ions was determined by the spectrophotometer (DR6000) according to the instructions provided by the HACH. Results: The concentration of nitrate and nitrite ions in all parts of the network was lower than the standard set by the WHO. The highest and lowest concentrations of nitrate and nitrite ions were obtained at the sampling sites of Patrice Restaurant (1.04 and 0.021 mg/L) and ABFA (0.8 and 0.0162 mg/L), respectively. Also, risk assessment based on the age range of infants, children and adults was 0.125, 0.00375 and 0.043, respectively, which shows that long-term water consumption will not have a negative impact on human health. Conclusion: The physicochemical quality of Evaz drinking water was acceptable and human exposure to this water has a non-carcinogenic risk of much less than the critical range.